Beetroot-pigment-derived colorimetric sensor for detection of calcium dipicolinate in bacterial spores. - Letícia Christina Pires Gonçalves (Public Library of Science (PLoS), 2013)
In this proof-of-concept study, we describe the use of the main red beet pigment betanin for the quantification of calcium dipicolinate in bacterial spores, including Bacillus anthracis. In the presence of europium(III) ions, betanin is converted to a water-soluble, non-luminescent orange 1∶1 complex with a stability constant of 1.4 × 10(5) L mol(-1). The addition of calcium dipicolinate, largely found in bacterial spores, changes the color of the aqueous solution of [Eu(Bn)(+)] from orange to magenta. The limit of detection (LOD) of calcium dipicolinate is around 2.0 × 10(-6) mol L(-1) and the LOD determined for both spores, B. cereus and B. anthracis, is (1.1 ± 0.3)× 10(6) spores mL(-1). This simple, green, fast and low cost colorimetric assay was selective for calcium dipicolinate when compared to several analogous compounds. The importance of this work relies on the potential use of betalains, raw natural pigments, as colorimetric sensors for biological applications.